Follow that man. Vol. 4 - Bellamy, Ralph, 1904-1991; Klee, Lawrence; Montagne, Edward J; McDonald, Frank; Berke, William; Alpha Video Distributors (Narberth, Pa. : Alpha Video Distributors, Inc., 2005)
"Ralph Bellamy stars as tough private-eye Mike Barnett in this lean and violent TV series Follow That Man (aka Man Against Crime) from the early 1950s..."--Container
Fuller's folly -- Hor fur -- Killer cat -- Main bout is murder
4 exciting episodes
Originally a television series from 1949-1954 and broadcast live until 1952
PUBLIC PERFORMANCE AND CLOSED CIRCUIT BROADCASTING RIGHTS NOT GRANTED
Created by Lawrence Klee
Ralph Bellamy
DVD
Keywords: Detectives -- New York (State) -- New York -- Drama; Detective and mystery television programs